2007
DOI: 10.1002/psp.466
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion or concentration for the 1.5 generation? Destination choices of the children of immigrants in the US

Abstract: This paper examines determinants of destination choice for foreign-born and 1.5 generation adult children of immigrants in the U.S. An immigrant concentrationweighted accessibility parameter is included to assess the spatial structure of destination AbstractThis paper examines determinants of destination choice for foreign-born and 1.5 generation adult children of immigrants in the U.S. An immigrant concentrationweighted accessibility parameter is included to assess the spatial structure of destination choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The use of the municipality as primary unit of analysis, in this study, makes it possible to capture a wide array of short‐distance and long‐distance movements between different types of places of origin and destination, and by covering the entire country, it is possible to extend the scale of many spatial studies of immigrants assimilation (for a review of works in this regard, see e.g. Goodwin‐White, ; further studies are cited in this article).…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the municipality as primary unit of analysis, in this study, makes it possible to capture a wide array of short‐distance and long‐distance movements between different types of places of origin and destination, and by covering the entire country, it is possible to extend the scale of many spatial studies of immigrants assimilation (for a review of works in this regard, see e.g. Goodwin‐White, ; further studies are cited in this article).…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…In this regard, the retaining or attracting power of immigrant concentrations is emphasised in many studies (e.g. Kritz and Nogle, ; Moore and Rosenberg, ; Liaw and Frey, ; Zavodny, ; Åslund, ; South et al ., ; Ellis and Goodwin‐White, ; Goodwin‐White, ; Le, ; Zorlu and Mulder, ; Tammaru and Kontuly, ; Kritz et al ., ; Xu, ). Likewise, in the literature, the estimated coefficients of variables indicating place of birth often remain significant when the rest of the variables are controlled for.…”
Section: Previous Research On the Spatial Redistribution Of Immigrantsmentioning
confidence: 99%
“…It may also not hold up when the relative wages of racial/nativity groups are considered visà-vis those of U.S.-born whites across an entire distribution of wages and when an intergenerational perspective on immigrants' economic progress is taken. This comparative approach graphically illustrates that relative position may be just as important in terms of considering immigrants' economic incorporation as absolute wages are and lends support to the suggestion that the contexts of labor market inequality vary geographically in ways that affect the progress of immigrants (for additional support for this argument and the link to immigrants' and the 1.5 generation's destination choices, see Goodwin-White 2007).…”
Section: Economic Geographymentioning
confidence: 59%
“…A recent attempt to link geographic context to spatial assimilation critiques found that metropolitan and state-level immigrant concentrations have continuing importance for the 1.5 generation's internal migration and choice of destination, with little evidence of negative economic effects (Ellis and Goodwin-White 2006;Goodwin-White 2007). The more specifically geographic (rather than sociological) nature of all this research has turned on the investigation of where immigrants and natives have what kinds of jobs and how the jobs are rewarded, rather than on cities as concentrations of immigrants.…”
Section: Geographic Perspectives On Immigrants and The Second Generationmentioning
confidence: 99%
“…With few exceptions (e.g., Goodwin-White 2007;Liaw et al 1986;Moore and Rosenberg 1995;Newbold 2007Newbold , 1999aShaw 1985;Trovato 1988), previous empirical studies have primarily used provinces, states or regions as the basic geographical units. Comprehensive research on internal migration at the metropolitan scale is hampered by the lack of appropriate data.…”
Section: Introductionmentioning
confidence: 99%